2021
DOI: 10.3390/biology10060550
|View full text |Cite
|
Sign up to set email alerts
|

Tristetraprolin, Inflammation, and Metabolic Syndrome in Arab Adults: A Case Control Study

Abstract: Tristetraprolin (TTP) is an mRNA binding protein suggested to have a substantial role in regulating the mRNA expression of numerous inflammatory factors, but data on TTP and its association with metabolic syndrome (MetS), a chronic low-grade inflammatory disorder, are scarce. We hypothesize that TTP may modulate MetS and its components. A total of 200 Saudi adults (aged 38.6 ± 8.3 years) were included in this cross-sectional study. Anthropometrics data were collected and fasting blood glucose taken for the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…We found also significant differences between males and females in serum hs-CRP and IL-6 levels among Congolese adults. Previous studies have reported gender differences in circulating hs-CRP and IL-6 levels, while Al-Daghri et al [24] and Zafar et al [25]. According to the present study, there was a significant correlation between hs-CRP and fasting TG in both gender.…”
Section: Discussionsupporting
confidence: 62%
“…We found also significant differences between males and females in serum hs-CRP and IL-6 levels among Congolese adults. Previous studies have reported gender differences in circulating hs-CRP and IL-6 levels, while Al-Daghri et al [24] and Zafar et al [25]. According to the present study, there was a significant correlation between hs-CRP and fasting TG in both gender.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies indicated MetS was related to inflammation responses. 24 , 25 In terms of WBC, neutrophils, and NLR as hematological indicators for MetS, the results were not consistent. The present study revealed that the MetS individuals had high level of WBC and neutrophils than non-MetS individuals.…”
Section: Discussionmentioning
confidence: 84%
“…Serum triglycerides ≥ 1.7 mmol/L was considered high [ 21 ]. Low HDL-cholesterol was defined as < 1.03 mmol/L in men and < 1.3 mmol/L in women [ 21 , 22 ]. Serum 25 (OH) vitamin D was determined using the LIAISON XL automated quantitative analyzer (DiaSorin, Saluggia, Italy).…”
Section: Methodsmentioning
confidence: 99%